1987
DOI: 10.1002/1098-108x(198709)6:5<593::aid-eat2260060503>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive correlates of bulimia: The bulimic thoughts questionnaire

Abstract: A 20‐item measure of the cognitive correlates of bulimia, the Bulimic Thoughts Questionnaire (BTQ), is developed. Confirmatory factor analysis supports a threefactor structure for this measure: Self‐Schema, Self‐Efficacy, and Salient Beliefs. Study 1 compares bulimic, obese, and normal women on these factors. Bulimics demonstrate larger body image (Self‐Schema), lower expectations regarding ability to maintain desirable weight (Self‐Efficacy), and greater frequency of thoughts relevant to bulimia (Salient Beli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…These are measures developed by Franko, Zuroff, and Rosenthal (1986); Phelan (1987);and Clark, Feldman, and Channon (1989). However, only one was developed using factor analysis or principal components analysis (Phelan, 1987) and, in this study, the three factors identified do not map onto a clear theory of eating disorders.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…These are measures developed by Franko, Zuroff, and Rosenthal (1986); Phelan (1987);and Clark, Feldman, and Channon (1989). However, only one was developed using factor analysis or principal components analysis (Phelan, 1987) and, in this study, the three factors identified do not map onto a clear theory of eating disorders.…”
Section: Introductionmentioning
confidence: 75%
“…However, only one was developed using factor analysis or principal components analysis (Phelan, 1987) and, in this study, the three factors identified do not map onto a clear theory of eating disorders. Neither of the other two studies distinguished different types of thought.…”
Section: Introductionmentioning
confidence: 89%
“…Two studies have assessed self-statements or automatic thoughts, 1 one in bulimia nervosa (Phelan, 1987) and one in anorexia nervosa (D.A. Clark, Feldman & Channon, 1989).…”
Section: Evidence For Hypotheses Derived From Cognitive Theoriesmentioning
confidence: 99%
“…In addition to criterion related validity, Phelan (1987) provides some preliminary data on the factor structure of her questionnaire but no data on the reliability or validity of the three factors identified. Clark and colleagues (D.A.…”
Section: Evidence For Hypotheses Derived From Cognitive Theoriesmentioning
confidence: 99%
“…Body weight self-schemata, as evaluated by the Bulimic Thoughts Questionnaire (BTQ; Phelan, 1987), have also distinguished bulimic individuals from obese and normal-weight controls. Despite being of normal weight, bulimics rated themselves on the BTQ as heavier on self-schema items than normal-weight controls.…”
mentioning
confidence: 99%